Implikasi Etika Bisnis Dalam Perdagangan Benih Lobster Menurut Hukum Internasional - Elvina Fardila (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
The aim to be achieved in this research is to find out the importance of business ethics in the lobster seed trade according to international law. The method used in this research is normative law using secondary data in the form of journals and books related to the chosen research theme. The results of this research show that international law is a benchmark in covering various business actions which contain various ethics that must be adhered to by various countries. international law that regulates which is contained in the Sustainable Development Goals (SDGs) as an international law that emphasizes the preservation of future generations where this leads to extinction which can result in losses for the next generation